ANALYSIS OF IMPACT OF COVID-19 ON E-COMMERCE (International Journal of Food and Nutritional Sciences, 2022)
Coronavirus impact the whole e-commerce of the world; it has changed the nature of business. According to research 52% of consumers avoiding to go brick and mortar shopping and crowded areas. Furthermore, 36% avoiding brick and mortar shopping until they get coronavirus vaccine. Coronavirus effects different on different nature of products, means the impact of COVID-19 on several product is very high and on some product less impact. Overall sale of e-commerce increases because of this virus, people avoiding to go out, keeping social distance and buying from home, working from home such as grocery e-commerce increases 74%. Moreover, the media usage also increased in this time and Facebook, google update their features to connect more people in single time such as Facebook introduce messenger for 44 people that is competing to Zoom. Similarly, Google also launched updated version.